KEMAHIRAN AUDITOR INTERNAL MENDETEKSI FRAUD DENGAN SKEPTISME PROFESIONAL, INDEPENDENSI, RED FLAGS DAN RELIGIUSITAS - Syiar Rinaldy; Asbi Amin (Universitas Sulawesi Barat, 2023)
This study aims to examine the effect of professional skepticism, independence, red flags, and religiosity of internal auditors to detect fraud. This research method uses a scientific method to test the proposed hypothesis and uses statistical data to draw conclusions. The population of this research is the internal auditors at the Makassar City Inspectorate Office, amounting to 39 people. The sampling technique used was saturated sampling technique. Data collection techniques in this study used a questionnaire that was distributed directly to the respondents. Multiple linear regression method was used for data analysis. The results of the study found that professional skepticism, independence, red flags and religiosity had a positive and significant effect on internal auditors' proficiency in detecting fraud